The development of cultural event strategy: Swot analysis and QSPM approach - Perdana, Muhamad Ari; Rusmawan, Putu Ngurah; Tyas, Inno Cahyaning; Febrian, Ayu Wanda (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
n order to support the Banyuwangi Rebound Movement, Pondoknongko Village Government has launched an Economic and Tourism Improvement Program in 2022 through the Pondoknongko Festival Event. The purpose of this research is to: find out the management of the Pondoknongko Festival event; identify potential cultural tourism attractions; identify internal and external factors for the development of cultural tourism events; and determine the priority order of alternative strategies for developing cultural tourism events in Pondoknongko Village. This study used a descriptive research method with a mixed-method approach, exploratory sequential design model. The analysis technique used is Internal External (IE) Matrix, Strengths, Weaknesses, Opportunities, Threats (SWOT) Matrix, and Quantitative Strategic Planning Matrix (QSPM). The results showed that the Pondoknongko Festival Event Management had been well implemented starting from the research stage, design, planning, coordination, to the evaluation stage; Pondoknongko Village has a variety of potential cultural tourism attractions that can be developed and packaged as cultural tourism event activities; the position of the development of cultural tourism events is in cell IV grow and build and 10 alternative strategies have been formulated with a priority strategy that can be applied is to arrange tour packages that are integrated with cultural tourism events in Pondoknongko Village.